The Phylogeny, Biodiversity, and Ecology of the Chloroflexi in Activated Sludge - Speirs, Lachlan B. M.; Rice, Daniel T. F.; Petrovski, Steve; Seviour, Robert J. (Frontiers in Microbiology, 2019)
It is now clear that several of the filamentous bacteria in activated sludge wastewater treatment plants globally, are members of the phylum Chloroflexi. They appear to be more commonly found in treatment plants designed to remove nitrogen (N) and phosphorus (P), most of which operate at long sludge ages and expose the biomass to anaerobic conditions. The Chloroflexi seem to play an important beneficial role in providing the filamentous scaffolding around which flocs are formed, to feed on the debris from lysed bacterial cells, to ferment carbohydrates and to degrade other complex polymeric organic compounds to low molecular weight substrates to support their growth and that of other bacterial populations. A few commonly extend beyond the floc surface, while others can align in bundles, which may facilitate interfloc bridging and hence generate a bulking sludge. Although several recent papers have examined the phylogeny and in situ physiology of Chloroflexi in activated sludge plants in Denmark, this review takes a wider look at what we now know about these filaments, especially their global distribution in activated sludge plants, and what their functional roles there might be. It also attempts to outline why such information might provide us with clues as to how their population levels may be manipulated, and the main research questions that need addressing to achieve these outcomes.